STRATEGI DAN EFETIVITAS PEMASARAN UNTUK MENINGKATKAN PENDAPATAN PEDAGANG ECERAN IKAN SEGAR DI PASAR TRADISIONAL ALOK MAUMERE NUSA TENGGARA TIMUR - Sarlina Noni; Adriana Maria Septenis; Yohanes Wangge; Apolonaris Rivaldo Hure (Universitas Cokroaminoto Palopo, 2025)
This study aims to examine the marketing strategies and their effectiveness in increasing the income of retail fresh fish traders at Alok Traditional Market in Maumere, East Nusa Tenggara. The research type used is qualitative with a case study approach. Primary data were obtained through in-depth interviews with one of the retail traders, Mr. Hendrikus Nong, who has extensive experience in fish selling. Other data sources include direct field observations and documentation related to the process of catching, storing, and selling fish. The interview results indicate that traders source fish from TPI Maumere and apply various strategies, such as direct sales at the market and door-to-door selling, as well as using storage methods with boxes filled with frozen ice to preserve freshness. The main obstacles faced include seasonal price fluctuations and high competition. Storing fish with ice blocks has proven to be more effective in maintaining freshness for up to three days. Additionally, traders utilize diversification strategies by transforming unsold fish into dried fish. The analysis shows that these marketing strategies can increase the traders' daily income. The findings suggest that appropriate marketing strategies and effective management can improve the income of fresh fish traders in traditional markets. This research recommends enhancing marketing innovation and inventory management to support business sustainability and increase traders' income.